Pengaruh Pertumbuhan Ekonomi, Angkatan Kerja, Indeks Pembangunan Manusia Dan Upah Minimum Terhadap Tingkat Penangguran Di Kota Medan - Pratama, Bagus Mulya; Rahmah, Tri Indah Fadhila; Dharma, Budi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study will examine the effect of Economic Growth, the Work Force, and the variable Human Development Index, Minimum Wage on Unemployment in Medan City. The type of research used in this case is quantitative research. The data in this study is secondary data in the form of data for 2016-2021. Sample The method used is saturated sampling. Hypothesis testing was carried out using Eviews 20.0 for windows by testing the independent variables, namely Economic Growth, Labor Force, and the variable Human Development Index, Minimum Wage, the dependent variable, namely Unemployment. The results of this study indicate that Economic Growth, the Labor Force, and the variable Human Development Index, Minimum Wage simultaneously have a significant effect on Unemployment.